2014
DOI: 10.1007/s10157-014-0976-z
|View full text |Cite
|
Sign up to set email alerts
|

Are the equations for the creatinine-based estimated glomerular filtration rate applicable to the evaluation of renal function in Japanese children and adult patients receiving chemotherapy?

Abstract: Concordance between eGFR and CCr in pediatric patients with a unilateral kidney should be assessed separately from that in patients with bilateral kidneys. In restricting calculation of eGFR to pediatric patients with bilateral kidneys and adult patients without little muscle mass, eGFR may be useful regardless of whether patients are receiving chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Although the Wright formula [ 5 ], the Martin formula [ 6 ], and the Jelliffe equation [ 7 ] are intended for the estimation of GFR in cancer patients, no method has been developed for estimating GFR specifically in Japanese cancer patients. Therefore, in regard to the CQ of whether eGFR is recommended for assessment of renal function for the adjustment of anticancer drug doses, we conducted literature searches upon establishing the following two questions: “Is eGFR based on serum Cr values an appropriate substitute for the gold standard of GFR based on clearance of inulin, 51Cr-EDTA, or I-125 sodium iothalamate?” and “Is eGFR an appropriate substitute for conventional Ccr calculated with the Cockcroft-Gault equation?” We found 12 studies that compared actual GFR to eGFR [ 14 25 ], three studies that compared actual Ccr to eGFR [ 26 – 28 ], and three studies that compared Ccr as calculated with the Cockcroft-Gault equation to formulas for eGFR and other such predictive formulas [ 29 – 31 ].…”
Section: Summary Of Guidelinesmentioning
confidence: 99%
“…Although the Wright formula [ 5 ], the Martin formula [ 6 ], and the Jelliffe equation [ 7 ] are intended for the estimation of GFR in cancer patients, no method has been developed for estimating GFR specifically in Japanese cancer patients. Therefore, in regard to the CQ of whether eGFR is recommended for assessment of renal function for the adjustment of anticancer drug doses, we conducted literature searches upon establishing the following two questions: “Is eGFR based on serum Cr values an appropriate substitute for the gold standard of GFR based on clearance of inulin, 51Cr-EDTA, or I-125 sodium iothalamate?” and “Is eGFR an appropriate substitute for conventional Ccr calculated with the Cockcroft-Gault equation?” We found 12 studies that compared actual GFR to eGFR [ 14 25 ], three studies that compared actual Ccr to eGFR [ 26 – 28 ], and three studies that compared Ccr as calculated with the Cockcroft-Gault equation to formulas for eGFR and other such predictive formulas [ 29 – 31 ].…”
Section: Summary Of Guidelinesmentioning
confidence: 99%
“…The studies by Funakoshi et al on the accuracy of the eGFR in Japanese patients with cancer were the only ones to compare the eGFR to actual measured GFR values [ 9 , 10 ], while others made comparisons with 24-h CCr. Inoue et al [ 19 ] studied the ratio of eGFR overestimated by ≥ 30% than the measured GFR; however, we did not include their study in this meta-analysis because their control was CCr rather than the measured GFR value, and they did not include cases where the eGFR was lower than the measured GFR value. Funakoshi et al compared the GFR values measured by inulin clearance with the CKD-EPI formula, the estimation formula of the Japanese Society of Nephrology, Cockcroft-Gault formula, and CCr obtained using 24-h urine specimens collected from 50 patients with cancer; the accuracy assessed by P30 was 92% for the formula developed by the JSN and the CKD-EPI formula.…”
Section: Comparison Of Egfr and Measured Gfrmentioning
confidence: 99%
“…Because serum CysC values are not influenced by muscle mass, unlike creatinine (20), CysC -eGFR rather than Cr -eGFR is recommended for assessments of renal function among patients with abnormal muscle mass than healthy matched controls. We reported that Cr-eGFR can overestimate the renal function of Japanese pediatric patients undergoing chemotherapy as they have less muscle mass than healthy children (6). Several reports suggest that CysC is more appropriate than creatinine for evaluating renal function in pediatric patients with malignancies (21,22).…”
Section: Discussionmentioning
confidence: 92%
“…The Cr -eGFR has been recommended for pediatric patients with chronic kidney disease (CKD), but CysC -eGFR should be used for patients with abnormal muscle mass because muscle mass affects serum creatinine levels. In pediatric patients with malignancies and lower muscle mass than healthy children, Cr -eGFR can overestimate their renal function and result in an overdose of chemotherapeutic agents (6). On the other hand, thyroid dysfunction (7), human immunodeficiency virus (HIV) infection (8), and medication with steroids or immunosuppressive agents can affect serum cystatin C (CysC) values (9 -11).…”
Section: Introductionmentioning
confidence: 99%